Metropolitane Farben der Europäisierung. Die Institutionalisierung von Strukturen der integrierten territorialen Investitionen vor dem Hintergrund bisheriger Zusammenarbeit in den Metropolregionen - Krukowska, Joanna; Lackowska, Marta (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
The paper focuses on the institutional solutions adopted in various Polish metropolitan regions due to the requirement to create structures facilitating the operation of Integrated Territorial Investment (ITI) in the 2014–2020 EU financial perspective. This phenomenon is analysed in the light of the process of the launching and functioning of metropolitan cooperation and of the concept of Europeanization. Our considerations are based on the assumption that past attempts to institutionalize metropolitan cooperation influence the process of the creation and functioning of ITI cooperation. Our research has confirmed this proposition. We found various reactions to the top-down incentive in all of the investigated metropolitan regions. In general four main types of situation are identified depending on past metropolitan cooperation and its relation to the ITI institutions. On the national level an interesting “double top-down” pressure was discovered, as the EU guidelines have been made much stricter by the Polish government, turning an incentive for local actors into a must. Finally, Integrated Territorial Investment has enlivened metropolitan governance in Poland, which is interesting to follow in the future, especially as it has no connection to other national regulations proposed for metropolitan regions.
Keywords: Europeanization; Metropolitan governance; Intermunicipal cooperation; Integrated Territorial Investment; Poland